Comparative Analysis of E-Cigarette Regulation in Indonesia, Thailand, and Brunei Darussallam - Fajri, M. Hisyam Nur; Madjid, Abdul; Istiqomah, Milda (Universitas Katolik Soegijapranata Semarang, 2025)
Abstract : This study examines the increasing trend of e-cigarette use among students in Indonesia compared to Thailand and Brunei Darussalam. This study aims to analyse the advantages and disadvantages of e-cigarette regulation in Indonesia as a new form of addictive substance, and to compare it with regulatory frameworks in other countries in the region. Using normative juridical methods, this study explores laws and policies from Indonesia, Thailand, and Brunei Darussalam. Findings show that although Indonesia imposes relatively high excise taxes on e-cigarettes, its regulations are less comprehensive compared to other countries. Regulatory gaps in terms of advertising, age restrictions, and waste management of e-cigarettes are still evident. The journal suggests strengthening Indonesia's regulatory framework by adopting best practices from other Southeast Asian countries such as Thailand and Brunei Darussalam to ensure public health protection and environmental safety.Abstrak : Penelitian ini mengkaji tren peningkatan penggunaan rokok elektrik di kalangan pelajar di Indonesia dibandingkan dengan Thailand dan Brunei Darussalam. Penelitian ini bertujuan untuk menganalisis kelebihan dan kekurangan regulasi rokok elektrik di Indonesia sebagai bentuk baru dari zat adiktif, dan untuk membandingkannya dengan kerangka regulasi di negara-negara lain di kawasan ini. Dengan menggunakan metode yuridis normatif, penelitian ini mengeksplorasi undang-undang dan kebijakan dari Indonesia, Thailand, dan Brunei Darussalam. Temuan menunjukkan bahwa meskipun Indonesia memberlakukan cukai yang relatif tinggi terhadap rokok elektrik, namun peraturannya kurang komprehensif dibandingkan dengan negara lain. Kesenjangan regulasi dalam hal periklanan, pembatasan usia, dan pengelolaan limbah rokok elektrik masih terlihat jelas. Jurnal ini menyarankan untuk memperkuat kerangka regulasi Indonesia dengan mengadopsi praktik-praktik terbaik dari negara-negara Asia Tenggara lainnya seperti Thailand dan Brunei Darussalam untuk memastikan perlindungan kesehatan masyarakat dan keamanan lingkungan.